Classic Rock Tours 2. Exploring a Famous Ophiolite: A Guide to the Bay of Islands Igneous Complex in Gros Morne National Park, Western Newfoundland, Canada - Kerr, Andrew (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2019)
Ophiolites are complex assemblages of ultramafic and mafic igneous rocks that are now widely considered to be pieces of ancient oceanic crust that were emplaced on to the continents courtesy of global plate tectonics. However, most examples were originally considered parts of enormous layered mafic intrusions and so were interpreted in that light. The new understanding of ophiolites in the late 1960s and early 1970s was a crucial part of the global Earth Science revolution, and they are now central to all plate tectonic models developed for ancient orogenic belts. Although their equivalence to oceanic crust is now well established, many ophiolites may not be ‘typical’ examples of such, and not all examples are identical. Most ophiolites likely formed in subduction-influenced environments rather than at mid-ocean ridges. Ophiolites remain important foci for research in the 21st century, and many questions remain about their environments of formation and especially their mechanisms of emplacement onto the continents. Although it was not the first to be seen as a relic of a vanished ocean, the Bay of Islands Igneous Complex in western Newfoundland is one of the best preserved and most easily accessible ophiolites in the world. In the late 20th century, research work in this area proved highly influential in understanding the oceanic crust, and in unravelling the diachronous events involved in the progressive destruction of an ancient stable continental margin as arcs and microcontinental blocks were accreted along it. Parts of the Tablelands Ophiolite lie within Gros Morne National Park, which is a UNESCO world heritage site because of its importance to our understanding of global tectonics. The wider region around the park also includes the Cabox Aspiring Geopark Project, now also in the process of seeking recognition through UNESCO. This article provides background information on ophiolites and the development of our ideas about them, and links this material to four self-guided field excursions that allow examination of many classic features. These excursions range from a collection of roadside outcrops, to some relatively easy hiking excursions on official National Park trails, and eventually to a more challenging off-trail hike that ascends to the summit plateau of the Tablelands to visit rare exposures of the Moho (the Mohorovičić Discontinuity, i.e. the lower boundary of the Earth’s crust) and the underlying upper mantle rocks. Collectively, the field stops should allow geologically-minded visitors to experience some amazing geology in a spectacular and sometimes surreal landscape.